The role of inspiratory muscle training in the management of asthma and exercise-induced bronchoconstriction - Shei, R. J.; Paris, H. L. R.; Wilhite, D. P.; Chapman, R. F.; Mickleborough, T. D. (The Physician and Sportsmedicine, 2016)
Asthma is a pathological condition comprising of a variety of symptoms which affect the ability to function in daily life. Due to the high prevalence of asthma and associated healthcare costs, it is important to identify low-cost alternatives to traditional pharmacotherapy. One of these low cost alternatives is the use of inspiratory muscle training (IMT), which is a technique aimed at increasing the strength and endurance of the diaphragm and accessory muscles of respiration. IMT typically consists of taking voluntary inspirations against a resistive load across the entire range of vital capacity while at rest. In healthy individuals, the most notable benefits of IMT are an increase in diaphragm thickness and strength, a decrease in exertional dyspnea, and a decrease in the oxygen cost of breathing. Due to the presence of expiratory flow limitation in asthma and exercise-induced bronchoconstriction, dynamic lung hyperinflation is common. As a result of varying operational lung volumes, due in part to hyperinflation, the respiratory muscles may operate far from the optimal portion of the length-tension curve, and thus may be forced to operate against a low pulmonary compliance. Therefore, the ability of these muscles to generate tension is reduced, and for any given level of ventilation, the work of breathing is increased as compared to non-asthmatics. Evidence that IMT is an effective treatment for asthma is inconclusive, due to limited data and a wide variation in study methodologies. However, IMT has been shown to decrease dyspnea, increase inspiratory muscle strength, and improve exercise capacity in asthmatic individuals. In order to develop more concrete recommendations regarding IMT as an effective low-cost adjunct in addition to traditional asthma treatments, we recommend that a standard treatment protocol be developed and tested in a placebo-controlled clinical trial with a large representative sample.